2014
DOI: 10.1260/0263-6174.32.2-3.181
|View full text |Cite
|
Sign up to set email alerts
|

Batch and Column Studies for the Removal of Lead from Aqueous Solutions Using Activated Carbons from Viticultural Industry Wastes

Abstract: (A.C. Deiana). # The term 'pomace' refers to lex (Spanish), which is the residue from the solvent extraction of grape seed oil. The study used both pomace and grape stalk, another agricultural waste from the grape industry, as precursors of activated carbon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The coefficient of correlation (R 2 = 0.96), suggesting that this model resulted in a good fit to the experimental data compared to Yoon Nelson model. The obtained results were compared with other studies where agricultural waste used for the removal of Pb (II) is as shown in ( Table 2 ) [ [51] , [52] , [53] , [54] , [55] ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coefficient of correlation (R 2 = 0.96), suggesting that this model resulted in a good fit to the experimental data compared to Yoon Nelson model. The obtained results were compared with other studies where agricultural waste used for the removal of Pb (II) is as shown in ( Table 2 ) [ [51] , [52] , [53] , [54] , [55] ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the outcomes K YN has been increased from 0.026 to 0.035 (min −1 ) as flow rate increases from 5 to 10 (mL/min), whereas the 50% of τ reduced from 202 to 91 min with an increase in flow rate as depicted in Table 3 . The lower the K YN value result revealed that the mass transfer by the diffusion inside the column was better and higher the K YN value indicated the lower diffusion for the column [ [51] , [52] , [53] ].…”
Section: Resultsmentioning
confidence: 99%
“…Several practices are applied to reduce lead concentration such as chemical precipitation, electrolysis, ion exchange, and adsorption (Deiana et al, 2014). From the thorough study of the literature, it is found that adsorption study is the best practice to remove lead ion concentration.…”
Section: Introductionmentioning
confidence: 99%
“…After oil extraction, the seeds form a lignocellulosic waste called lex. 18,19 Both wastes, stalk and seed lex, are currently used to produce only energy by burning and the development of products with added value from these wastes is of considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…It can be inferred that this surface carbon formed by grape must decomposition plays an important role during the reaction as suggested in Figure 9. 19 In fact, it has been suggested 10,11 that carbons can behave like the quinone-reductase enzymes, where the combination of quinone redox group with an efficient electron transport system is considered the key-features for an efficient catalyst. A similar mechanism can be proposed for the reaction in the presence of the activated carbon briquettes (Figure 9).…”
mentioning
confidence: 99%